Deep geothermal sources for electricity production in Slovakia: thermal conditions - MAJCIN, Dušan; KRÁL, Miroslav; BILČÍK, Dušan; ŠUJAN, Martin; VRANOVSKÁ, Andrea (Contributions to Geophysics and Geodesy, 2020)
The contribution presents the results of geothermic interpretation approaches applied to measured geothermal data and is focused to determination of the thermal conditions both for application of classic hydrothermal sources exploitation and specialized EGS technologies for electricity production in the region of Slovakia and adjacent areas. Primarily, the heat flow density data and the temperature distribution measurements in boreholes were interpreted by classic 1D interpolation and extrapolation methods. New terrestrial heat flow density map for the studied area was constructed using the values determined in boreholes, their interpretations, the newest outcomes of geothermal modelling methods based both on steady-state and transient heat transfer approaches, and on other recently gained geoscientific knowledge. Thereafter, we constructed the maps of temperature field distribution for selected depth levels up to 6000 m below the surface and the final map of the isothermal surface depths for the reservoir temperature of 160 °C. This final map serves for the appraisal of the effective application of the binary cycle power plant technology in Slovakia in terms of thermal conditions.